Field testing and performance optimization of a weld reinforcement device in heavy haul railways. (January 2023) - Liu, Guangpeng; Xiao, Hong; Shi, Guangming; Zhang, Moyan; Nadakatti, Mahantesh M; Gu, Mu
The Bowed plates weld device (BPWD) is a new type of rail weld reinforcement device, which has been widely applied in heavy haul railway lines in China. It changes the service state and vibration characteristics of a weld. In order to explore the BPWD vibration influence on the track, static, and dynamic on-site tests were carried out on a heavy haul line. The vibration influence and spectrum characteristics of the track between BPWD and unplated weld (UW) was compared. At the same time, a 3D coupling model of heavy haul train-rail weld was established and optimization of service performance of the BPWD was carried out. The results showed that the average acceleration of rail, sleeper and ballast at the BPWDwere 52.7%, 43.5%, and 50.2% lower than that of UW. In comparison with UW, peak value of the periodic frequency spectrum and dominant frequency distribution in the BPWD track structure could be effectively reduced from rails to ballast. Length of 0.8 m for plate was found to be optimum in order to reduce the rail stress effectively. The material of the insulating interlayer should preferably be nylon.